2018
DOI: 10.4062/biomolther.2017.054
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Sulfur Amino Acid Metabolism in Male C57BL/6 Mice

Abstract: Alterations in sulfur amino acid metabolism are associated with an increased risk of a number of common late-life diseases, which raises the possibility that metabolism of sulfur amino acids may change with age. The present study was conducted to understand the age-related changes in hepatic metabolism of sulfur amino acids in 2-, 6-, 18- and 30-month-old male C57BL/6 mice. For this purpose, metabolite profiling of sulfur amino acids from methionine to taurine or glutathione (GSH) was performed. The levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Jeon et al reported a significant decrease with age in plasma glutathione and hepatic homocysteine levels when comparing 2, 6, and 18 months old C57BL/6 male mice. While the level of the other sulfur-containing amino acids were not different among those age groups, the concentration of sulfur-containing amino acids was significantly affected in the liver of 30-months old mice (49). Interestingly, we observed a significant increase in the total sulfur blood plasma concentration in aged mice (40-65 weeks) compared to young controls (14-28 weeks), suggesting that total plasma sulfur concentration is not an indicator of the status of sulfur-containing amino acids in blood plasma.…”
Section: Discussionmentioning
confidence: 78%
“…Jeon et al reported a significant decrease with age in plasma glutathione and hepatic homocysteine levels when comparing 2, 6, and 18 months old C57BL/6 male mice. While the level of the other sulfur-containing amino acids were not different among those age groups, the concentration of sulfur-containing amino acids was significantly affected in the liver of 30-months old mice (49). Interestingly, we observed a significant increase in the total sulfur blood plasma concentration in aged mice (40-65 weeks) compared to young controls (14-28 weeks), suggesting that total plasma sulfur concentration is not an indicator of the status of sulfur-containing amino acids in blood plasma.…”
Section: Discussionmentioning
confidence: 78%
“…Hence, using the same concentration of Met (0.12%) in the SAAR diet for adult mice might not result in the same level of restriction as in young. Aging alters the transsulfuration pathway, which could affect the magnitude of CR and CR‐specific changes (Jeon et al, 2018 ). Future studies should try SAAR diets with less than 0.12% Met to increase the efficacy in adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly considering the redox balance, in ET-FPP ® mice we have much higher antioxidants levels and a greater reduction of ROS than in LT-FPP ® mice. The plasma levels of antioxidants, in particular GSH and SOD-1, usually decrease with increasing age [64][65][66][67], therefore in the case of LT-FPP ® mice, FPP ® induces an increase in GSH and SOD-1, but starting from lower basal levels, thus failing to trigger a minimally comparable anti-aging action.…”
Section: Discussionmentioning
confidence: 99%